Using ultrasound for renal fat thickness measurements to predict body fat in Dorper ewe lambs - Muñoz-Osorio, GA; Garcia -Herrera, RA; Peralta-Torres, JA; Vázquez- Martínez, I; Gastelum-Delgado, MÁ; Meza-Villalvazo, VM; Vargas-Bello-Pérez, E; Chay-Canul, A (Journal of the Hellenic Veterinary Medical Society, 2025)
This study determined the relationship between kidney fat thickness (KFT), measured by ultrasound and body fat depots in Dorper ewe lambs. Twenty ewe lambs of six months of age (body weight 36.53±25 kg) were used. The subcutaneous fat thickness (SFT), depth (LTD, cm), width (LTW, cm), and area (LTMA, cm2) of the longissimus thoracis muscle and KFT were measured by ultrasound 24 h before slaughter. After slaughtering, the carcass weight (HCW) was recorded. The carcass was then chilled for 24 hours at a temperature of 1°C and reweighed (CCW) halved along the dorsal midline. The left half of the carcass was dissected into muscle, fat (subcutaneous fat plus intermuscular fat, CF), and bone, and each of these tissues was weighed separately and were adjusted to give the total weight of the carcass. Internal fat (IF) was removed, weighed, and categorized as mesenteric (MF), omental (GO), or perirenal (GP) fat deposits. Total IF weight was the sum of these depots. The total weight of total body fat (TBF) was calculated as the sum of the IF plus the CF. KFT ranged from 0.27 to 0.80 cm. Similarly, the TBF ranged from 2.41 to 6.38 kg. KFT was moderately associated with internal fat stores (0.65 ≤ r ≤ 0.79, P < 0.001). In addition, PLT and ALT had a low level of association with CF. The results showed that KFT had a moderate association with internal body fat (0.65 ≤ r ≤ 0.79, P < 0.001). However, it was weakly associated with CF (r=0.42). All equations had low to moderate precision (0.57 ≤ r2 ≤ 0.81). However, all equations had high accuracy (bias correction factor > 0.94). It is also important to note that Dorper lambs in this study tended to store more fat in the carcass than in the internal depots. The results of this study support the use of KFT as a non-invasive method for predicting body fatness in hair sheep.